Sequence and phylogenetic analysis of the mitochondrial genome for the Poyang Lake, Misgurnus anguillicaudatus (natural diploid loach). Issue 3 (2nd July 2020) - Zhang, Guisheng; Zhang, Hongmei; Zhao, Guihong; Yang, Xi; Zhang, Tian; Liu, Qiang; Wang, Yan; Zhang, Guosong; Zhu, Daoyu
: Misgurnus anguillicaudatus is a highly valued, aquaculture-relevant food fish in East Asian countries. In this study, the complete mitochondrial genome of Poyang loach was obtained by PCR. The genome is 16, 646 bp in length, including 2 ribosomal RNA genes. 13 protein-coding genes, 22 transfer RNA genes, and a non-coding control region, the gene composition and order of the species were similar to most reported from other vertebrates. The phylogenetic tree showed that Misgurnus family got together for one branch, which includes Poyang M. anguillicaudatus, and the other loaches had their own branches.